The impact of tourism sector variables on economic growth in the Kingdom of Saudi Arabia during the period 2010-2020 - Elgzoli, Ebtihag Hashim Mohammed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study examines the influence of tourism sector variables on economic growth in the Kingdom of Saudi Arabia from 2010 to 2020. Employing a descriptive theoretical framework and an analytical approach, the research employs GARCH models to assess the impact of tourism revenues, general revenues, and investments in the tourism sector on economic growth. Through diagnostic tests, the findings reveal significant correlations: firstly, a positive relationship exists between tourism revenues and economic growth; secondly, a positive correlation is observed between general revenues and economic growth; thirdly, there is a positive correlation between investments in the tourism sector and economic growth. Moreover, the study underscores the explanatory capacity of tourism sector variables in economic growth and the predictive accuracy of the estimated model in forecasting economic growth via tourism sector variables in Saudi Arabia. Consequently, these results offer valuable insights for analysis, policy evaluation, and economic decision-making within the Saudi Arabian tourism sector. The study provides recommendations including comprehensive analysis of internal and external tourism environments to identify strengths, weaknesses, opportunities, and threats; attention to the quality of tourist services to reflect the cultural and humanitarian values of Saudi Arabia; and enhancing collaboration with institutions supporting tourism activity such as transportation, healthcare, education services, and border control agencies.